PKM HIDROPONIK BAGI SISWA DAN GURU IPA DI SMAN 4 KELURAHAN UJUNG BULU KECAMATAN UJUNG KOTA PARE-PARE - Ralle, Andi; Alimuddin, Suraedah (Jurnal BALIRESO, 2022)
The implementation of school hydroponics can create the creativity of teachers and students in cultivating plants so that they can support science learning, especially biology. School hydroponics can also instil character education in students and make students more concerned about environmental sustainability. Our partners in this service activity are a group of students and science teachers at SMAN 4 Pare-pare which consists of 25 people. The school is located in Ujung Bulu Village, Ujung District, Parepare City. Teachers and students have simply made school hydroponics, but the results they get are still minimal so they need counseling and assistance in managing the hydroponics. The problems faced by partners are seed nursery, plant maintenance, and post-harvest handling. The purpose of this service is to improve the knowledge and skills of partners in the application of the vegetable hydroponic system in schools and post-harvest handling. The implementation method used is counseling, and plot demonstration. monitoring and evaluation. This service activity received very good appreciation from students and teachers, they enthusiastically and enthusiastically participated in a whole series of activities from preparation to evaluation of activities. This service activity succeeded in increasing the knowledge and skills of students and teachers in implementing hydroponic vegetable cultivation technology (lettuce and celery) and post-harvest handling